Unpacking purchase decisions: What drives consumer to choose hypermarket brand product? - Mohd Din, Adilah; Abdul Rahim, Nur Nadhirah; Othman, Azrina; Mohamad, Norhidayah (Human Resource Management Academic Research Society, 2024)
This research explores the factors influencing consumer purchase decisions for hypermarket brand products in Melaka, Malaysia. As hypermarkets play a critical role in the retail landscape, understanding what drives consumer choices is essential for hypermarket managers to remain competitive. Grounded in Keller’s Customer-Based Brand Equity (CBBE) Model and the Engel Kollat Blackwell (EKB) Model of Consumer Behavior, the study examines the effects of four key factors: store image, customer loyalty, sales promotions, and product quality. A survey of 380 hypermarket shoppers was conducted through online and in-store methods. Data analysis using SPSS version 27, including descriptive statistics, Pearson correlation, and multiple regression, revealed that all four factors significantly affect consumer purchase decisions, with product quality being the most influential. The findings emphasize the importance of delivering high-quality products to enhance customer satisfaction and loyalty. The study's scope was limited to hypermarkets in Melaka, which may affect the generalizability of the results. Future research should expand to include other regions in Malaysia and examine additional factors, such as pricing strategies and digital marketing, to gain a more comprehensive understanding of consumer behavior in the retail industry.